Strengthening the Profile of Pancasila Students through Extracurricular Scouts in Elementary Schools - Risalatul Meiana, Putri; Minsih (Universitas Pendidikan Ganesha, 2023)
Education has developed rapidly in line with existing technological developments, but all of that also affects students' character. For this reason, the government provides policies regarding strengthening the profile of Pancasila students. There have been many efforts that can be made to strengthen the profile of Pancasila students. However, there are still few efforts to strengthen the profile of Pancasila students through Scout extracurriculars. Therefore, this study aims to analyze the strengthening of the profile of Pancasila students through scout extracurricular activities in elementary schools. This type of research is qualitative research. This research uses a qualitative descriptive approach. The research was carried out using technical triangulation and source triangulation. The technical triangulation used was interviews, documentation, and observation, while the source triangulation used was scout teachers and students. Data whose legitimacy is proven can be carried out by analyzing data reducing data, displaying data, and drawing conclusions. The results of this study indicate that scout extracurricular activities can strengthen the profile of Pancasila students from all aspects. Students can practice Pancasila values through the application of Pancasila student profiles. In the future, Scout extracurricular activities can be maximized so that students can absorb aspects of the Pancasila student profile well.